The Effect of John Zahorek's Model on the Development of Reflective Thinking among Second Grade Students - Al – Khafaji, Raed; Al – Qaisi, Taha (Journal of Tikrit university for humanities - مجلة جامعة تكريت للعلوم الانسانية, 2019)
The research aims to identify the effect of John Zahorek's model on the development of the contemplative thinking of second-grade students. In order to achieve the goal of the research, the researchers followed the procedures of the experimental method. The researchers prepared a teaching plan according to Zahorek. The researchers confirmed their validity by presenting them to a group of experts and arbitrators.  The researcher chose randomly the intermediate school of Hassan al-Sumaida'i to represent the experimental group that was taught according to the model of John Zahorek by 30 students and the average displaced to represent the control group which is taught according to the usual method by 34 students belonging to the General Directorate of Salahuddin Governorate. In fact,  the researcher prepared the test of contemplative thinking and be of (20) paragraph of the type of multiple choice, after being confirmed the validity and stability, the researchers used the following statistical means: (the test of the two independent samples, Pearson correlation coefficient, and equation Alpha Kronbach). After analyzing the results statistically, the researchers reached the following:1. There are statistically significant differences between the experimental and control groups in the test of reflective thinking in favor of the experimental group The researchers reached a number of conclusions: The effectiveness of John Zahorek's model in the development of contemplative thinking among second-grade students in Islamic education. .Through the findings of the researchers, a number of recommendations and proposals were presented